Preparation method and application of electro-catalytic ammonia production catalyst based on perovskite material in-situ A-site and B-site doping
By in-situ A and B doping on perovskite materials, the LaCeMnNiO3 catalyst was prepared, which solved the problems of low catalytic activity and efficiency of existing catalysts, and achieved efficient electrocatalytic ammonia production, and significantly improved ammonia production and Faraday efficiency.
Patent Information
- Application Number
- CN202411856223.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The catalytic activity and catalytic efficiency of existing electrocatalytic nitrite ammonia production catalysts are low, making it difficult to effectively promote the kinetics of NO2RR reactions and reduce side reactions.
By doping perovskite (LaMnO3) in situ A and B positions, an excellent LaCeMnNiO3 catalyst was prepared, and the reaction path was controlled by the synergistic action of Ce and Ni to improve the selectivity of ammonia and Faraday efficiency.
It significantly improves catalytic activity and stability, and achieves excellent electrocatalytic ammonia production performance, with high ammonia production and high Faraday efficiency, reaching more than 95%.
Smart Images

Figure CN119685853A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrocatalytic ammonia production catalyst and a preparation method thereof. Background Art
[0002] Ammonia is not only an important component for industry and agriculture, but also a clean energy for hydrogen carrier. The commercial method for producing NH3 is the Haber-Bosch process, which involves a large amount of energy consumption and serious environmental problems. In the past few years, considerable attention has been paid to the synthesis of ambient NH3 by electrocatalytic N2 reduction. Nevertheless, the solubility of N2 is extremely low, the N triple bond is very stable, and the NRR seriously competes with the hydrogen evolution reaction, resulting in the NH3 Faradaic efficiency and NH3 yield being far from satisfactory. Alternatively, nitrite not only exhibits high water solubility but also has a lower N double bond O bond dissociation energy. At the same time, NO2 - NO2 is a ubiquitous nitrogen-based pollutant in soil and groundwater, causing significant environmental and public health problems worldwide. - Reduction to NH3 (NO2RR) has great potential to simultaneously mitigate NO2 - Pollutants are removed and valuable NH3 is produced. However, achieving selective NO2RR involves a complex six-electron process, which requires efficient catalysts to promote NO2RR reaction kinetics while minimizing side reactions including HER. Existing perovskite catalysts LaMnO3 have low catalytic activity and efficiency when used to catalyze such reactions. Summary of the invention
[0003] The present invention aims to solve the technical problem of low catalytic activity and catalytic efficiency of existing electrocatalytic nitrite ammonia production catalysts, and provides a preparation method and application of an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials, and prepares a catalyst with excellent performance by in-situ doping of perovskite (LaMnO3). Lanthanum manganate has excellent conductivity and good mechanical and chemical stability. By performing in-plane doping in the A and B sites, the catalytic activity and stability can be significantly improved, and excellent electrocatalytic ammonia production performance can be achieved.
[0004] The preparation method of the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite material of the present invention is carried out according to the following steps:
[0005] 1. Add lanthanum salt, manganese salt, cerium salt, nickel salt, citric acid and ethylenediaminetetraacetic acid into water, add ammonia water to adjust the pH of the mixed solution to 6-6.5 during stirring, and continue stirring for 2-2.5 hours to obtain a precursor solution;
[0006] 2. placing the precursor solution obtained in step 1 in a water bath and heating it to obtain a gel;
[0007] 3. After drying the gel described in step 2, calcining it in a muffle furnace to obtain an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite material, represented by LaCeMnNiO3.
[0008] Furthermore, the lanthanum salt described in step 1 is one or more of lanthanum nitrate, lanthanum chloride and lanthanum sulfate.
[0009] Furthermore, the manganese salt in step 1 is one or more of manganese nitrate, manganese chloride and manganese sulfate.
[0010] Furthermore, the cerium salt in step 1 is one or both of cerium nitrate and cerium chloride.
[0011] Furthermore, the nickel salt described in step 1 is one or more of nickel nitrate, nickel chloride and nickel sulfate.
[0012] Furthermore, the molar ratio of the lanthanum salt: manganese salt: cerium salt: nickel salt described in step 1 is (0.1-1): (0.1-1): (0.005-0.05): (0.005-0.05).
[0013] Furthermore, the ratio of the amount of the lanthanum salt in step 1 to the volume of water is (0.1-1) mol: (10-100) mL.
[0014] Furthermore, the ratio of the mass of citric acid, the mass of ethylenediaminetetraacetic acid and the volume of water described in step 1 is (1-145) g:(5-20) g:(10-100) mL.
[0015] Furthermore, the heating temperature in step 2 is 70-90° C., and the heating time is 1-6 hours.
[0016] Furthermore, the drying temperature in step three is 50-80° C., and the drying time is 6-12 hours.
[0017] Furthermore, the calcination temperature in step three is 700-1000° C., and the calcination time is 2-6 hours.
[0018] The application of the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite material prepared by the above method is to prepare the catalyst into an electrode for use in electrocatalytic nitrite / nitrate ammonia production.
[0019] Furthermore, the method for preparing an electrode using an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of a perovskite material is as follows: preparing a slurry of the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of a perovskite material, coating the slurry on a carbon paper or carbon cloth substrate, and obtaining a non-self-supporting perovskite-based catalyst.
[0020] The high-efficiency electrocatalytic ammonia production catalyst (LaCeMnNiO3) doped with in-situ A-site and B-site of the perovskite material prepared by the present invention has the advantages that the reduction process of nitrite is often accompanied by the generation of byproducts (such as NO, N2O), and the synergistic effect of Ce and Ni can effectively control the reaction path and improve the selectivity and Faraday efficiency of ammonia. The rare earth properties of Ce (oxygen vacancy generation ability, f orbital effect) and the transition metal properties of Ni (conductivity improvement, electron density optimization) are combined to prepare a new type of perovskite catalyst. The preparation process of this composite material is relatively simple and low-cost, with high controllability, mild reaction conditions, small footprint and environmental friendliness, and has good prospects for industrial application.
[0021] The LaCeMnNiO3 composite material of the present invention is used in electrocatalytic nitrite to produce ammonia, which has the characteristics of high ammonia yield and high Faraday efficiency. The ammonia production amount is 11941 μg·cm at a voltage of -0.8V. -2 ·h -1 , the Faraday efficiency reaches more than 95%. The high-efficiency electrocatalytic ammonia production catalyst doped with the in-situ A-site and B-site of the perovskite material prepared by the present invention can be used in the field of electrocatalytic nitrite ammonia production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD pattern of LaCeMnO3 electrocatalyst prepared in Example 1;
[0023] Figure 2 This is a scanning electron microscope image of the LaCeMnO3 electrocatalyst prepared in Example 1;
[0024] Figure 3 The ammonia production and Faraday efficiency of the LaCeMnO3 electrocatalyst prepared in Example 1 for reducing nitrite;
[0025] Figure 4 XRD pattern of LaMnNiO3 electrocatalyst prepared in Example 2;
[0026] Figure 5 The ammonia production and Faraday efficiency of the LaMnNiO3 electrocatalyst for reducing nitrite prepared in Example 2;
[0027] Figure 6 XRD pattern of LaCeMnNiO3 electrocatalyst prepared in Example 3;
[0028] Figure 7 This is a scanning electron microscope image of the LaCeMnNiO3 electrocatalyst prepared in Example 3;
[0029] Figure 8 This is a diagram of ammonia production and Faraday efficiency of nitrite reduction by the LaCeMnNiO3 electrocatalyst prepared in Example 3. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The various raw materials used in the following embodiments are commercially available unless otherwise specified.
[0031] Embodiment 1: The preparation method of the LaCeMnO3 catalyst of this embodiment is carried out according to the following steps:
[0032] 1. Add 5.04 g of LaN3O9·6H2O, 3.01 g of MnN2O6·4H2O, 0.156 g of CeN3O9·6H2O, 11.53 g of citric acid and 7.014 g of ethylenediaminetetraacetic acid into 40 mL of water, slowly add appropriate amount of ammonia water under stirring to adjust the pH to 6, and stir for 2 hours to obtain a precursor solution;
[0033] 2. Put the precursor solution obtained in step 1 into a water bath at 85°C and stir at 85°C for 4 hours to obtain a gel;
[0034] 3. Place the gel in an oven and dry it at 50°C for 12 hours to obtain a dry gel; then place the dry gel in a muffle furnace, heat it to 900°C and keep it for 2 hours for calcination to obtain a LaCeMnO3 catalyst.
[0035] The XRD pattern of the LaCeMnO3 catalyst prepared in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the characteristic peaks of the XRD spectrum of LaCeMnO3 match the standard card pdf#09-6038, further confirming that LaCeMnO3 was successfully synthesized. At the same time, the sharp characteristic peaks confirm that the catalyst has good crystallinity. In addition, the absence of other impurity peaks further confirms that the doping of Ce is in-plane doping.
[0036] The scanning electron microscope image of the LaCeMnO3 catalyst prepared in Example 1 is as follows Figure 2 As shown, from Figure 2 It can be seen that the catalyst surface is composed of nanoparticle structures with a diameter of 30 to 80 nm. These small nanoparticles provide a larger specific surface area and thus provide more exposed active sites.
[0037] 3 mg of the LaCeMnO3 catalyst prepared in Example 1 was mixed with 0.5 mL of ethanol and 0.1 mL of ultrapure water and ultrasonicated for 30 min to prepare a slurry, which was then coated on a carbon paper substrate and dried to obtain an electrode. The loading of the LaCeMnO3 catalyst on the electrode was 1 mg cm -2 ; coated on a carbon paper substrate as the working electrode (cathode) in the electrocatalytic nitrite ammonia production reaction, with a silver / silver chloride electrode as the reference electrode and a platinum electrode as the counter electrode connected to an electrochemical workstation (Chenhua 760e), and tested in an H-type electrolytic cell. The ammonia production and Faraday efficiency of the LaCeMnO3 catalyst prepared in Example 1 for nitrite reduction at different negative voltages are shown in the figure. Figure 3 As shown, from Figure 3 It can be seen that the ammonia production reached 4768 μg cm -2 ·h -1 , the Faradaic efficiency reached 85%, confirming the excellent performance of the catalyst.
[0038] Example 2: The preparation method of the LaMnNiO3 electrocatalyst of this example is carried out according to the following steps:
[0039] 1. Add 5.04 g of LaN3O9·6H2O, 3.01 g of MnN2O6·4H2O, 0.149 g of NiC4H6O4·4H2O, 11.53 g of citric acid and 7.014 g of ethylenediaminetetraacetic acid to 40 mL of water, slowly add appropriate amount of ammonia water under stirring to adjust the pH to 6, and stir for 2 hours to obtain a precursor solution;
[0040] 2. Put the precursor solution obtained in step 1 into a water bath at 85°C, stir at 85°C for 4 hours to obtain a gel; then put it into an oven and dry it at 50°C for 12 hours.
[0041] 3. Place the gel in an oven and dry it at 50°C for 12 hours to obtain a dry gel; then place the dry gel in a muffle furnace, heat it to 900°C and keep it for 2 hours for calcination to obtain a LaMnNiO3 catalyst.
[0042] The XRD pattern of the LaMnNiO3 catalyst prepared in Example 2 is as follows Figure 4 As shown, from Figure 4 It can be seen that the characteristic peaks of the XRD spectrum of LaMnNiO3 match the standard card pdf#09-6038, further confirming that LaMnNiO3 was successfully synthesized. At the same time, the sharp characteristic peaks confirm that the catalyst has good crystallinity. In addition, no other impurity peaks were found, further confirming that the doping of Ni is in-plane doping.
[0043] The surface of the LaMnNiO3 catalyst prepared in Example 2 is composed of nanoparticle structures with a diameter of 30 to 80 nm. Such small nanoparticles provide a larger specific surface area and thus provide more exposed active sites.
[0044] 3 mg of the LaMnNiO3 catalyst prepared in Example 1 was mixed with 0.5 mL of ethanol and 0.1 mL of ultrapure water and ultrasonicated for 30 min to prepare a slurry, which was then coated on a carbon paper substrate and dried to obtain an electrode. The loading of the LaMnNiO3 catalyst on the electrode was 1 mg cm -2 ; This electrode was used as the working electrode (cathode) in the electrocatalytic nitrite ammonia production reaction, the silver / silver chloride electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The electrochemical workstation (Chenhua 760e) was connected to test in an H-type electrolytic cell. The ammonia production and Faraday efficiency of the LaMnNiO3 catalyst prepared in Example 2 for nitrite reduction at different negative voltages are shown in the figure. Figure 5 As shown, from Figure 5 It can be seen that the ammonia production of the LaMnNiO3 catalyst prepared in Example 2 reaches 8315 μg·cm -2 ·h -1 , the Faradaic efficiency reached 85%, confirming the excellent performance of the catalyst.
[0045] Example 3: The preparation method of the electrocatalytic ammonia production catalyst LaCeMnNiO3 based on the in-situ A-site and B-site doping of the perovskite material in this example is carried out according to the following steps:
[0046] 1. Add 5.04 g of LaN3O9·6H2O, 0.156 g of CeN3O9·6H2O, 3.01 g of MnN2O6·4H2O, 0.149 g of NiC4H6O4·4H2O, 11.53 g of citric acid and 7.014 g of ethylenediaminetetraacetic acid to 40 mL of water, slowly add appropriate amount of ammonia water under stirring to adjust the pH of the mixed solution to 6, and stir for 2 hours to obtain a precursor solution;
[0047] 2. Put the precursor solution obtained in step 1 into a water bath at 85°C, stir at 85°C for 4 hours to obtain a gel; then put it into an oven and dry it at 50°C for 12 hours.
[0048] 3. Dry the gel obtained in step 2 in an oven at 50°C for 12 hours to obtain a dry gel; then place the dry gel in a muffle furnace, heat it to 900°C and keep it for 2 hours for calcination to obtain an electrocatalytic ammonia production catalyst LaCeMnNiO3 based on in-situ A-site and B-site doping of perovskite material.
[0049] The XRD pattern of the LaCeMnNiO3 catalyst prepared in Example 3 is as follows: Figure 6 As shown, from Figure 6 It can be seen that the characteristic peaks of the XRD spectrum of LaCeMnNiO3 match the standard card pdf#09-6038, further confirming that LaCeMnNiO3 was successfully synthesized. At the same time, the sharp characteristic peaks confirm that the catalyst has good crystallinity. In addition, no other impurity peaks were found, further confirming that the co-doping of Ce and Ni is in-plane doping.
[0050] The scanning electron microscope image of the LaCeMnNiO3 catalyst prepared in Example 3 is as follows Figure 7 As shown, from Figure 7 It can be seen that the catalyst surface is composed of nanoparticle structures with a diameter of 30 to 80 nm. These small nanoparticles provide a larger specific surface area and thus provide more exposed active sites.
[0051] 3 mg of the LaCeMnNiO3 catalyst prepared in Example 1 was mixed with 0.5 mL of ethanol and 0.1 mL of ultrapure water and ultrasonicated for 30 min to prepare a slurry, which was then coated on a carbon paper substrate and dried to obtain an electrode. The loading of the LaCeMnNiO3 catalyst on the electrode was 1 mg cm -2 ; This electrode was used as the working electrode (cathode) in the electrocatalytic nitrite ammonia production reaction, the silver / silver chloride electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. The electrochemical workstation (Chenhua 760e) was connected to test in an H-type electrolytic cell. The ammonia production and Faraday efficiency of the LaCeMnNiO3 catalyst prepared in Example 3 for nitrite reduction at different negative voltages are shown in the figure. Figure 8 As shown, from Figure 8 It can be seen that the ammonia production of the LaCeMnNiO3 catalyst prepared in Example 3 reaches 11941 μg·cm -2 ·h -1 , the Faraday efficiency reaches 95%, and its ammonia production is 2.5 times that of the LaCeMnO3 catalyst in Example 1, 1.44 times that of the LaMnNiO3 catalyst in Example 2, and the Faraday efficiency is increased by 11.8%. It is confirmed that the LaCeMnNiO3 catalyst has excellent performance. It shows that the ammonia production and Faraday efficiency are greatly improved by in-situ in-plane co-coating of Ce and Ni on the lanthanum manganate substrate. This is because Ce mainly enhances adsorption and activation capabilities through oxygen vacancy regulation and surface electronic structure optimization, while Ni enhances activity through electron density regulation and reaction path optimization. The synergistic effect of the two significantly improves the catalytic performance and selectivity, resulting in a 1+1>2 effect. The LaCeMnNiO3 catalyst is an efficient and stable perovskite catalyst.
[0052] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials, characterized in that The method proceeds as follows:
1. Add lanthanum salt, manganese salt, cerium salt, nickel salt, citric acid and ethylenediaminetetraacetic acid into water, add ammonia water to adjust the pH of the mixed solution to 6-6.5 during stirring, and continue stirring for 2-2.5 hours to obtain a precursor solution; 2. placing the precursor solution obtained in step 1 in a water bath and heating it to obtain a gel; 3. After drying the gel described in step 2, calcining it in a muffle furnace to obtain an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite material, represented by LaCeMnNiO3.
2. The method for preparing the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1, characterized in that The lanthanum salt described in step 1 is one or more of lanthanum nitrate, lanthanum chloride and lanthanum sulfate.
3. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The manganese salt described in step 1 is one or more of manganese nitrate, manganese chloride and manganese sulfate.
4. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The cerium salt described in step 1 is one or both of cerium nitrate and cerium chloride.
5. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The nickel salt described in step 1 is one or more of nickel nitrate, nickel chloride and nickel sulfate.
6. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The molar ratio of the lanthanum salt: manganese salt: cerium salt: nickel salt described in step 1 is (0.1-1): (0.1-1): (0.005-0.05): (0.005-0.05).
7. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The ratio of the amount of the lanthanum salt described in step 1 to the volume of water is (0.1-1) mol: (10-100) mL.
8. The method for preparing an electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 1 or 2, characterized in that: The calcination temperature in step 3 is 700-1000° C., and the calcination time is 2-6 hours.
9. Application of the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials prepared by the method of claim 1, characterized in that This application is to prepare an electrode based on the electrocatalytic ammonia production catalyst doped in situ at the A and B sites of the perovskite material for use in the electrocatalytic production of ammonia from nitrite / nitrate.
10. The use of the electrocatalytic ammonia production catalyst based on in-situ A-site and B-site doping of perovskite materials according to claim 9, characterized in that: The method for preparing an electrode using an electrocatalytic ammonia production catalyst doped at in-situ A and B sites of a perovskite material is as follows: preparing a slurry of the electrocatalytic ammonia production catalyst doped at in-situ A and B sites of a perovskite material, coating the slurry on a carbon paper or carbon cloth substrate, and obtaining a non-self-supporting perovskite-based catalyst.